Mutual Fund Industry Selection and Persistence - BUSSE, Jeffrey A. (Institutional Knowledge at Singapore Management University, 2012)
We analyze mutual fund industry selectivity — the performance of a fund’s industry allocation relative to the market. We find that industry selection accounts for a full third of fund performance based on two-digit SIC codes, with the remaining attributable to the performance of individual stocks relative to their own industries. We find that industry-selection skill drives persistence in relative performance, particularly over longer investment horizons. Unlike individual-stock-selection ability, industry selectivity is not eroded by increasing fund assets. Our results suggest that accounting for a manager’s ability to pick outperforming industries provides information beyond standard performance measures that can enhance a fund investor’s future performance.